TEKNIK LAYANAN SIRKULASI PERPUSTAKAAN UPT. PERPUSTAKAAN UNIVERSITAS UDAYANA - Widya Putri, Ni Putu Melati; Ginting, Richard Togaranta; Kawitri Resen, Putu Titah (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT The study purpose was determined the circulation library service technique of UPT Udayana University Library. The study was described descriptively of circulation library service techniques and compare with circulation library service theoretical. Main data the study collected through interviews and secondary data used literature review. The results showed that the circulation library service technique at UPT. Udayana University Library has been implementing Standard Operation Procedure (SOP) of Circulation Library Service. The Library SOP arranged and based of kinds of library theoretical review. It is hoped to continue and support by using RFID technology to impove the circulation library service. Keyword: service, circulation service, UPT. Udayana University Library